Comparison of Safety and Efficacy of Pregabalin versus Gabapentin for the treatment of Uremic Pruritus in Patients with Chronic Kidney Disease on Maintenance Haemodialysis - Ravindran, Ashima (Indian J Palliat Care, 2020)
BACKGROUND: Uremic pruritus (UP) affects many patients suffering from chronic kidney disease (CKD) and has a negative impact on the quality of life. The severity of UP ranges from sporadic discomfort to complete restlessness during both day and night time. It has become increasingly evident that central transmission and sensitization processes similar to those observed in chronic pain are important mechanisms of pruritus. METHODOLOGY: This was a randomized single-blind prospective-interventional study carried out for 6 weeks. Male and female patients aged between 20 and 85 years with end-stage renal disease undergoing maintenance hemodialysis and who had substantial pruritus defined as persistent were included in our study. Informed consent was obtained from each patient before enrolling in the study. Patients were randomly divided into two groups (Group A and B), with Group A receiving pregabalin 25 mg and Group B receiving gabapentin 100 mg. The efficacy and safety of drugs were assessed after 6 weeks using visual analog scale and 5D itch scale. RESULTS: We used gabapentin 100 mg or pregabalin 25 mg for 42 consecutive patients with CKD on maintenance hemodialysis with a mean age of patients in Group A (pregabalin 25 mg) 55.29 ± 14.58 and B (gabapentin 100 mg) 58.10 ± 11.09. Both gabapentin and pregabalin produced a significant difference in itching intensity with P < 0.001; however, there was no statistically significant difference between the effectiveness of two drugs in reducing itch. While receiving gabapentin, 11 of 21 patients (52.38%) reported fatigue, dizziness, somnolescence, which was statistically significant (P ≤ 0.001) and 4 of these patients discontinued use of the drug due to excessive somnolence, all after the first dose. A statistically significant difference was found in each domain of 5D-Pruritus scale after gabapentin and pregabalin therapy.